Gene polymorphisms and risk of idiopathic pulmonary fibrosis: a systematic review and meta-analysis - Maryam Hassan; Akbar Shoukat Ali; Ali Bin Sarwar Zubairi; Zahra Ali Padhani; Salman Kirmani; Huzaifa Ahmad; Zafar Fatmi; Jai K Das (Monaldi Archives for Chest Disease, 2024)
Idiopathic pulmonary fibrosis (IPF) has been widely hypothesized to occur as a result of an interplay between a nexus of environmental and genetic risk factors. However, not much is known about the genetic aspect of this disease. The objective of this review was to identify the genetic polymorphisms associated with the risk of developing IPF. We searched PubMed, EBSCO CINAHL Plus, Web of Science, and Wiley Cochrane Library databases for studies on risk factors of IPF published between March 2000 and November 2023. Studies with an IPF diagnosis based only on the American Thoracic Society and the European Respiratory Society guidelines were included. Thirty-one case-control studies were included with 3997 IPF and 20,925 non-IPF subjects. Two of the studies enrolled biopsy-proven IPF patients; 13 studies diagnosed IPF on the basis of clinical and high-resolution computed tomography (HRCT) findings; and 14 studies diagnosed based on both biopsy and clinical and HRCT findings. 16 studies with MUC5B rs35705950, IL-4 rs2243250, IL-4 rs2070874, and tumor necrosis factor α (TNFα)-308 were eligible for meta-analysis. The allele contrast model (T versus G) for MUC5B rs35705950 revealed statistically significant association of T allele with the risk of IPF [odds ratio (OR) 3.84, 95% confidence interval (CI) 3.20 to 4.61, adjusted p<0.0001), as was the allele contrast model for Asian (OR 2.83, 95% CI 1.51 to 5.32, adjusted p=0.009) and Caucasian (OR 4.11, 95% CI 3.56 to 4.75, adjusted p<0.0001). The allele contrast models for IL-4 rs2243250, IL-4 rs2070874, and TNFα-308 did not demonstrate any significant association with IPF. This review suggests an association of MUC5B rs35705950 T allele with the risk of developing IPF. To our knowledge, this study is the first to aggregate several genetic polymorphisms associated with IPF.